Using a Web GIS Plate Tectonics Simulation to Promote Geospatial Thinking. Issue 4 (2nd November 2016) - Bodzin, Alec M.; Anastasio, David; Sharif, Rajhida; Rutzmoser, Scott
ABSTRACT: Learning with Web-based geographic information system (Web GIS) can promote geospatial thinking and analysis of georeferenced data. Web GIS can enable learners to analyze rich data sets to understand spatial relationships that are managed in georeferenced data visualizations. We developed a Web GIS plate tectonics simulation as a capstone learning activity in an undergraduate Earth Science course that integrated geological and geophysical data sets to allow students to dynamically reconstruct ancient plate motions. To assess the effectiveness of the Web GIS tectonics simulation, all 12 students in the course submitted three artifacts that were assessed with a reliable, criterion-based rubric. The students also completed a survey to assess the effectiveness of the online interface and its capability to promote geospatial thinking. The students preformed quite well on the assignment. The survey results supported that the students perceived the Web GIS tectonics simulation as having helped them think geospatially. Our Web GIS design and embedded capabilities allowed students to advance and confirm their understandings about the tectonics concepts. Student responses indicated that the Web GIS supported their geospatial analysis for making inferences about space, geospatial patterns, and geospatial relationships among the data that were visualized in the Web GIS. Design features that contributed to the successful implementation are discussed.